P563 Monitoring of vedolizumab drug levels in a treat to target strategy for moderate-severe IBD (MOVE-IBD). (30th January 2023) - Logan, H; Rimmer, K; Doecke, J; Patrick, D
Abstract: Background: Vedolizumab is an effective drug in moderate-severe ulcerative colitis (UC) and Crohn's disease (CD). A previous link between drug exposure and clinical response has been suggested in the literature making therapeutic drug monitoring (TDM) for vedolizumab an attractive idea to try and optimize patient outcomes. Recent data from the ENTERPRET induction study in UC presented at Digestive Diseases 2022 suggest no advantage to dose optimizing based on vedolizumab levels. Thus, there is discordance in the literature regarding the clinical relevance of vedolizumab drug levels. We aimed to clarify the utility of proactive TDM of vedolizumab trough levels in our cohort of maintenance vedolizumab patients using objective markers of disease activity in a treat to target strategy. Methods: A single-centre retrospective cross sectional cohort study using proactive TDM was performed on 84 patients with moderate to severe IBD on vedolizumab maintenance therapy. All patients were receiving standard vedolizumab dosing of 300 mg every eight weeks. A vedolizumab trough drug level was paired with clinical and objective markers of disease activity. The two endpoints examined were steroid free clinical remission and objective remission. Objective remission targets were individualized for each patient using a treat to target strategy and benchmarked against a baseline abnormal test. Steroid free clinical remission was defined in Crohn's disease as a Crohn's disease activity index (CDAI) of < 150 and in ulcerative colitis as a partial MAYO score of < 1 in a patient off steroids. Objective remission was defined as faecal calprotectin < 150 ug/g, normal bowel wall thickness on intestinal ultrasound or magnetic resonance imaging without associated features of inflammation or absence of ulceration on colonoscopy or sigmoidoscopy within 3 months of the vedolizumab level. Results: Median trough vedolizumab levels for patients were numerically higher but not statistically different in patients who had achieved steroid free clinical remission (13.3 ug/ml vs 8.89 ug/ml p = 0.544) or objective remission (15.22 ug/ml vs 10.28 ug/ml p = 0.139). See Figures 1. In addition, quartile analysis showed no statistically significant difference between quartiles of vedolizumab levels and clinical or objective remission (p = 0.822). Conclusion: Trough serum vedolizumab levels in our real-life cohort of maintenance moderate severe IBD patients were not associated with clinical or objective remission. Caution should be applied to basing treatment decisions off vedolizumab maintenance levels until more data becomes available to support its routine use in clinical practice.